Dynamic maskless optical lithography - Hilario, Paul Leonard Atchong C.
We propose techniques for dynamic and maskless optical lithography. We construct the experimental set-ups for these techniques and evaluate the performance of the set-ups in terms of the resolution. We first construct a beam scanning, set-up which directly write the pattern on the photoresist sample. The resolution of the set-up is calculated using Richards and Wolf and compared to the experimentally measured width of the voxel. The experimentally measured width is around 1.02 µm which is smaller than the calculated width of the pointspread function of 1.7 µm. Based on the comparison, we are able to determine the threshold of the sample and hence establish a regime of numerical apertures by which the dominating factor is the response of the photoresist and a regime where the dominating factor is the diffraction. Axial resolution was computed from Richards and Wolf and was found to be around 2 µm.